Stress-induced sex differences in spatial naviagation - Amod, Alyssa R (Department of Psychology, 2017)
Certain forms of spatial navigation are centered, neuroanatomically, on the hippocampal formation, a brain structure vulnerable to increased levels of the stress hormone cortisol. Although empirical studies have identified a substantial sex difference, in favor of males, on laboratory-based spatial navigation tasks, little research has investigated whether, and how, these sex differences manifest under conditions of psychological or physiological stress. The current study aimed to resolve some of the inconsistencies in the literature, and to investigate the relations between stress and performance in male and female participants. The current study followed a mixed quasi-experimental pretest-posttest design in which men (n = 23) and women (n = 23) were tested on two separate days (the first day under control conditions and the second under stressful conditions). I utilized a novel stress induction paradigm (the Fear Factor Stress Test) that would produce both hypothalamic-pituitary-adrenal axis and autonomic nervous system activity in men and women, and created a spatial navigation virtual environment task that would allow for cue usage of both landmarks and gradients. Participants also completed the Card Rotations Test as an assessment of their mental rotation abilities. I hypothesized that (a) men would perform better on spatial navigation tasks than women on Day 1 (i.e., the control condition) despite the availability of landmark cues, and (b) stress would affect spatial navigation performance in women more than in men. Results suggested that the stressor used was effective in eliciting appropriate responses in both men and women, however women showed smaller cortisol increases than men, relative to baseline. Regarding the navigation task, under unstressed conditions men showed a steeper learning curve than women in an unchanged environment, and performed better than women only when a proximal landmark cue was removed from the environment. Furthermore, findings suggested that acute psychosocial stress enhanced navigational performance in men, but impaired such performance in women. Regarding the mental rotation task, no sex differences were observed under unstressed conditions; however, under the stressed condition men improved in their performance whereas women were relatively unaffected. It appears then that men's spatial ability might, under particular conditions and on particular tasks, be enhanced following exposure to a stressor. Furthermore, the pattern of results observed in the spatial navigation task suggests that the types of navigation-aiding cues in an environment (as well as location of these cues relative to the target) play a significant role in eliciting sex differences in navigational performance following exposure to a psychosocial stressor.